Gynaecological Cancers Risk Breast Cancer, Ovarian Cancer and Endometrial Cancer - Manchanda, Ranjit (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The International Agency for Research on Cancer suggests that the burden of women's cancers including breast, ovarian, and womb will rise by 50% over the next 20 years. It is essential for us to improve early diagnosis and prevention of these cancers in our health systems. The last decade has seen significant strides in our ability to understand and predict a woman's risk of these cancers and offer personalized medicine approaches for risk management. There have been improvements in identifying individuals at increased risk, as well as implementing and evaluating strategies for screening and prevention. In this special collection, we bring together 16 articles from leading scientists and researchers. These capture some of the important advances observed in estimating cancer risk, providing genetic testing, offering risk management to those at increased risk, as well as screening and prevention of breast, ovarian, and womb cancers in women. This makes an important contribution to the rapidly advancing knowledge base across the area of personalized medicine and precision prevention of ovarian, endometrial, and breast cancers.